2007 IEEE/MTT-S International Microwave Symposium 2007
DOI: 10.1109/mwsym.2007.380530
|View full text |Cite
|
Sign up to set email alerts
|

FCC compliant 3.1-10.6 GHz UWB Pulse Radar System using Correlation Detection

Abstract: Abstract-A short range 3.1 -10.6 GHz single band ultrawideband (UWB) pulse radar system is presented. The transmitter consists of a pulse generator that is connected to a broadband monopole antenna. The generated pulse shape is similar to the fifth derivative of the Gaussian bell shape and makes efficient use of the allocated FCC UWB frequency mask. The receiver is realized with a single-ended low noise amplifier and active single-ended to differential converters that drive the input ports of an analog correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…The received power Figure 1. Receiver architecture based on the receivers in [7,10,11]. P r at a distance d is [12]:…”
Section: Design Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The received power Figure 1. Receiver architecture based on the receivers in [7,10,11]. P r at a distance d is [12]:…”
Section: Design Parametersmentioning
confidence: 99%
“…1, according to our simulations, the required sampling time is ∆t = 10 ps. Thus, according to [11], for a phase-offset of receiver clock ∆Φ Rx = 360 • , ∆t = 1 360 * ∆Φ Rx * f PRF = 10 ps for a receiver clock frequency f PRF = 300 MHz. In [16] it was shown that the number of bits n = 4 bits is sufficient for reliable detection of UWB signals ‡ .…”
Section: Power Consumptionmentioning
confidence: 99%
“…Considering power consumption constraints, we assume the use of an analog sliding-correlator as proposed in [13]. The sampling interval in analog correlation is represented as time-shift.…”
Section: Proposed Rrcr Ranging Techniquementioning
confidence: 99%
“…The sampling interval in analog correlation is represented as time-shift. In our system, we assume a sampling interval (time-shift) = 10 ps, similar to [13]. Sliding-correlator determines the TOA of the signal of the strongest path [3]: where, τ peak is the TOA of the strongest path.…”
Section: Proposed Rrcr Ranging Techniquementioning
confidence: 99%
See 1 more Smart Citation